Pathways to Recidivism for Women Released From Prison: A Mediated Model of Abuse, Mental Health Issues, and Substance Use. (September 2019) - Tripodi, Stephen; Pettus-Davis, Carrie; Bender, Kimberly; Fitzgerald, Michael; Renn, Tanya; Kennedy, Stephanie
This study uses structural equation modeling to determine whether there are direct and indirect relationships between childhood trauma and recidivism for 230 women from two state prisons in North Carolina. The researchers obtained a random sample from all women scheduled to be released between 30 and 120 days from data collection. Findings indicated that childhood trauma was not significantly related to recidivism for this sample, but there was an indirect relationship with depression being the intervening variable accounting for the relationship between childhood trauma and recidivism. Results lend support to the importance of addressing incarcerated women's trauma before release, while also assessing for depression and using empirically supported interventions to treat depression when applicable.